Luminescence Properties of Silicate Mineral: Charoite - KHANLARY*†, M.; TOWNSEND, P. (Asian Journal of Chemistry, 2009)
Luminescence measurements of charoite are reported which includetwo main emission bands centred near 380 and 600 nm. There are minordifferences in response between cathodoluminescence and radioluminescenceand greater differences between light and dark coloured charoite.For a dark sample, there is an additional band near 820 nm which has adiscontinuity in intensity near 170 ºC. This feature is ascribed to loss ofwater bonded into the structure. Models for the emission bands in thisgem stone are consistent with earlier proposals.